Automatic Synthesis and Micro PET/CT Imaging Study of 11C-DASB as a Serotonin Imaging Agent - ZHANG Xiao-jun; LI Yun-gang; ZHANG Jin-ming (Journal of Isotopes, 2015)
Objectives: Automatic synthesis of 11C-DASB as a serotonin imaging agent was established and Micro PET/CT imaging with Wistar rat was performed. Methods: Optimization of 11C-DASB synthesis was established by modifying different 11C-methylation agents, solvent and reaction conditions. Automated procedure for the synthesis of 11C-DASB was established, and Micro PET/CT imaging was complied with Wistar rat. Results: The optimized 11C-DASB synthesis was obtained. When 11C-CH3-Triflate was used as methylation agent, 500 μL DMSO was used to dissolve 1 mg precursor, the reaction was carried out at 80 ℃ for 2 min, the radiochemical synthesis yield was 63.7%. Micro PET/CT studies in rat showed that the initial uptake of 11C-DASB in the brain was high, especially in region of the highest density of SERT, such as colliculus and mid brain. Conclusion: The study should provide the basis for routine preparations of 11C-DASB with high reliability, it may be useful for PET imaging of SERT binding sites in the brain.